Measurement of Banking Performance in a Dynamic Multiactivity Network Structure: Evidence from Banks in Taiwan. Issue 4 (3rd April 2017) - Chao, Chuang-Min; Yu, Ming-Miin; Lee, Yun-Ting; Hsiao, Bo
ABSTRACT: In this study, we develop a dynamic multi-activity network DEA (DMNDEA) model that combines the multi-activity network DEA model (MNDEA) with the dynamic network DEA model (DNDEA). This new model is used to measure the efficiency of twenty-seven Taiwanese banks under a multistage and multiactivity production process during the sample period of 2006–12. The proposed model is able to identify whether inefficiencies stem from financial activities or the production stages and provides managers with information to propose better strategies to improve the overall performance of their banks under fluid macroeconomic conditions across time.